ESPISTEMOLIGICAL REFLECTIONS ABOUT POLITICAL AND CULTURAL MEDIATIONS IN SCHOOL PHYSICAL MOVING: CASE STUDY DEVELOPED IN A SCHOOL OF BASIC EDUCATION OF THE MANGUEIRA/RJ (Fiep Bulletin - online, 2012)
The article presents epistemological reflections about the Political and Cultural Mediation held in Physical Moving classes at Municipal School Humberto de Campos, located in Mangueira/RJ. From empirical observations, we developed a case study during five months, aiming at understanding the processes of conflict resolution and mediation occurred in Physical Moving classes. During the first analysis, we observe and describe how the propositions of Educational techniques and Physical Moving are consistent with the principles of mediation, especially when it comes to political values, cultural and social. Considering the proximity Gremio Recreativo Escola de Samba Mangueira and Mangueira Olympic Village, the axiology of art, culture and sport was debated together with the technical applicability and Educational activities. We discuss the role of Physical Moving professional in the processes of conflict resolution and mediation.